PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN SUGGESTIONS AND OFFERS - AAN SAJIATMOJO (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
Based on the description of the research results that have been presented, the researcher draws conclusions from the results of research conducted at SMA Negeri 2 Tanjung Selor, namely that there is an increase in the learning outcomes of class XI IPA students at SMA Negeri 2 Tanjung Selor in the Subject of Suggestions and offers. In the pre-cycle 7 students who studied thoroughly, then increased in cycle 1 there were 21 students who completed learning and in cycle 2 reached 29 students. The percentage of student completeness shows in the pre-cycle 22.2%, then increases to 66.6% in cycle 1 and becomes 94.4% in cycle 2. Then research with the problem "Application of Experiential Learning Models in Improving Student Learning Outcomes on the Subject Suggestions and offers in Class XI IPA SMA Negeri 2 Tanjung Selor Academic Year 2019/2020", in a process and a short period of time, the Experiential Learning Learning Model has a positive impact on students, namely students in class XI Science can improve their learning outcomes on the subject matter of Suggestions and offers. ABSTRAKBerdasarkan uraian hasil penelitian yang telah dipaparkan, maka peneliti membuat kesimpulan dari hasil penelitian yang dilakukan di SMA Negeri 2 Tanjung Selor yaitu terdapat peningkatan Hasil Belajar siswa kelas XI IPA  SMA Negeri 2 Tanjung Selor  pada Pokok Bahasan Suggestions and offers. Pada pra siklus 7 siswa yang tuntas belajar, kemudian meningkat pada siklus 1 ada 21 siswa yang tuntas belajar dan pada siklus 2 mencapai 29 siswa. Presentase ketuntasan siswa menunjukkan pada pra siklus 22,2 %, kemudian meningkat menjadi 66,6 % pada siklus 1 dan menjadi 94,4 % pada siklus 2. Maka penelitian dengan permasalahan "Penerapan Model Pembelajaran Experiential Learning Dalam Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Suggestions and offers  Di Kelas XI IPA  SMA Negeri 2 Tanjung Selor Tahun Ajaran 2019/2020", dalam proses dan jangka waktu yang tidak pendek, Model Pembelajaran Experiential Learning tersebut berdampak positif bagi siswa yaitu siswa kelas XI IPA bisa meningkatkan Hasil Belajarnya Pada Pokok Bahasan Suggestions and offers.